Diagnosis of delayed cerebral ischemia in patients with aneurysmal subarachnoid hemorrhage and triggers for intervention - Abdulazim, Amr Nabil; Heilig, Marina; Rinkel, Gabriel J. E.; Etminan, Nima (Neurocritical care, 2023)
Delayed cerebral ischemia (DCI) is a major determinant for poor neurological outcome after aneurysmal subarachnoid hemorrhage (aSAH). Detection and treatment of DCI is a key component in the neurocritical care of patients with aSAH after initial aneurysm repair.